Power electronics basics operating principles, design, formulas, and applications - Rozanov, I︠U︡. A. (I︠U︡riĭ Anatolʹevich) 1934-; Ryvkin, Sergey; Chaplygin, E. E. (Evgeniĭ Evgenʹevich); Voronin, Pavel (CRC Press, 2016)
This book provides fundamental knowledge for the analysis and design of modern power electronic devices. This text: Explains the basic concepts and most important terms of power electronics ; Describes the power assemblies, control, and passive components of semiconductor power switches ; Covers the control of power electronic devices, from mathematical modeling to the analysis of the electrical processes ; Addresses pulse-width modulation, power quality control, and multilevel, modular, and multicell power converter topologies ; Discusses line-commutated and resonant converters, as well as inverters and AC converters based on completely controllable switches ; Explores cutting-edge applications of power electronics, including renewable energy production and storage, fuel cells, and electric drives. This book supplies graduate students, industry professionals, researchers, and academics with a solid understanding of the underlying theory, while offering an overview of the latest achievements and development prospects in the power electronics industry